Perceived quality of life: towards a generic measure in Nigerian culture (2009)
This study was designed to develop and validate a generic perceived quality of life measure for Nigerian culture so as to ensure culture relevance and validity of the concept of quality of life. One hundred and twenty-two (122) randomly selected respondents with ages ranging from 18-60 years old, a mean age of 28. 7 and standard deviation of 9.9 took part in the study. The sample was drawn from Lagos, the former capital of Nigeria and, Ibadan, the capital of Oyo State. Results show that the measure has content validity (using 80% agreements of experts). Reliability coefficient alpha is .87while standardized item , alpha is .87 with correlation between forms of. 68. Principal Component Analysis (PCA) brought out , seven factors,' contentment, relationship, _social support, self-competence, self-health perception, environmental relationship and recreation. It was thus concluded that this scale is a valid measure of perceived quality of life among Nigerians. It also suggested that the study can be improved upon to investigate multi-ethnic differences in perception of quality of life.